Change and determinants of total and context specific sitting in adults: A 7-year longitudinal study. Issue 6 (June 2020) - Wennman, Heini; Härkänen, Tommi; Hagströmer, Maria; Jousilahti, Pekka; Laatikainen, Tiina; Mäki-Opas, Tomi; Männistö, Satu; Tolonen, Hanna; Valkeinen, Heli; Borodulin, Katja
Abstract: Objectives: To assess the stability and determinants of total and context specific sitting in a follow-up of adults. Design: Longitudinal study. Methods: Participants in the DILGOM cohort (n = 3735, men 45%), reported daily sitting in five contexts (work-related, in vehicle, at home by the TV, at home at the computer, and elsewhere) in 2007 and 2014. Sociodemographic background, lifestyle and health were assessed in 2007. Total sitting comprised the sum of context specific sitting. Changes in, and determinants of context specific sitting, stratified by baseline age into young middle-aged (<53 years); late middle-aged (53–68 years) and older-aged (>68 years) were estimated by generalized linear mixed models. Results: In 2007, total daily sitting was 7 h 26 min, 6 h 16 min, and 6 h 3 min in young middle-aged, late middle-aged and older-aged groups, respectively. Over 7 years, total sitting decreased on average by 26 min. Sitting at the computer increased by 7–17 min. The late middle-aged group also increased sitting by the TV, and decreased total, work-related, vehicle and elsewhere sitting. Occupational status determined context specific sitting, but somewhat differently in young and late middle-aged groups. Poor self-rated health determined less work-related and more sitting by the TV in the young, whereas good health determined less work-related sitting in the late middle-aged group. Conclusions: Self-reported sitting is a fairly stable behavior, with the exception for the late middle-aged group, where all context specific and total sitting changed significantly. Occupational status and health determined changes in sitting; however, somewhat differently by age group.